EXAMINING THE ASSOCIATIONS BETWEEN GESTATIONAL AGE AND HEAD CIRCUMFERENCE IN THE SECOND TRIMESTER: A CROSS-SECTIONAL STUDY - Nandini, Vijay; Sinha, Arti; Prasad, Rashmi; Gupta, Amit (Student’s Journal of Health Research Africa, 2024)
Background: Accurate estimation of gestational age is crucial for optimal prenatal care, and fetal biometry, particularly head circumference (HC), plays a significant role in this assessment. Previous studies suggest that HC measurements during the second trimester can provide reliable indicators of gestational age, but further investigation is needed to establish their effectiveness across diverse populations. Aim: To evaluate the correlation between gestational age and head circumference measurements in singleton pregnancies during the second trimester. Methods: A study was conducted involving 100 pregnant women between 20 and 38 weeks at each gestational week. Participants were selected based on specific inclusion and exclusion criteria. Head circumference measurements were obtained via ultrasound, and gestational age was calculated using an average of three HC values. Statistical analyses included Pearson correlation coefficients and regression analysis to determine the relationship between HC and gestational age. Results: 100 women were enrolled, with an average maternal age of 29.5 years (±4.8) and a pre-pregnancy BMI of 24.0 (±4.8). The analysis revealed a strong positive correlation between HC measurements and gestational age (Pearson r = 0.89, p < 0.001). Most participants (51%) had HC measurements ranging from 148 to 159 mm, corresponding to a gestational age of 18+0 to 18+6 weeks. Conclusion: The findings indicate that head circumference is a highly reliable indicator for estimating gestational age during the second trimester. The established regression equations provide a useful tool for predicting gestational age based on HC measurements. Recommendations: Future research should involve larger, multicentric studies to validate these findings and develop population-specific reference tables for fetal biometry. This will enhance the accuracy of gestational age estimation and improve prenatal care strategies tailored to diverse populations.